2014
DOI: 10.1111/bjop.12097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of average household income and damage exposure on post‐earthquake distress and functioning: A community study following the February 2011 Christchurch earthquake

Abstract: Post-traumatic stress, depression and anxiety symptoms are common outcomes following earthquakes, and may persist for months and years. This study systematically examined the impact of neighbourhood damage exposure and average household income on psychological distress and functioning in 600 residents of Christchurch, New Zealand, 4-6 months after the fatal February, 2011 earthquake. Participants were from highly affected and relatively unaffected suburbs in low, medium and high average household income areas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 62 publications
3
24
1
Order By: Relevance
“…Responses to functioning in the first four areas were averaged to obtain a score for disruptions in general life functioning ('general functioning'), while the latter three were averaged to get a score for disruptions to relationship functioning ('relationship functioning'). Breaking the items in this way was confirmed by factor analysis (See Dorahy et al, 2015).…”
Section: Methodsmentioning
confidence: 80%
See 2 more Smart Citations
“…Responses to functioning in the first four areas were averaged to obtain a score for disruptions in general life functioning ('general functioning'), while the latter three were averaged to get a score for disruptions to relationship functioning ('relationship functioning'). Breaking the items in this way was confirmed by factor analysis (See Dorahy et al, 2015).…”
Section: Methodsmentioning
confidence: 80%
“…For each of these affected suburbs a matched suburb based on demographic variables (e.g., number of people in suburb, their average age and gender) and socioeconomic level was found that was relatively unaffected by the earthquake. These three suburbs experienced less overall damage to homes and properties and had minimal loss of utilities (see Dorahy et al, 2015). …”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Another study showed that 6 months after the 2011 Christchurch earthquake in New Zealand, on average lower income per home contributed unequivocally to earthquake-related distress and dysfunction. 27 A recent study also showed that 6 months after the Great East Japan Earthquake tsunami experience, property loss and poverty were associated with PTSD in patients with cardiovascular disease and had an adverse prognostic impact. 24 This study showed that living in evacuation shelters or temporary housing, rather than one's own home, was associated with exacerbation of all the examined cardiovascular symptoms, and the statistical results were more robust in women than in men.…”
Section: Discussionmentioning
confidence: 98%
“…Low income may be considered a chronic stressor, increasing psychological distress as a result of limited access to resources and opportunities for accumulation of resources. 27 Previous studies have shown that, following an earthquake, living in a low-income area may contribute to greater psychological distress due to a lack of occupational, social and financial resources. A community study revealed that, after the Christchurch earthquake, low household income contributed strongly to earthquake-related distress.…”
Section: Discussionmentioning
confidence: 99%